Gestão de pessoas: integração e motivação em contexto de pressão por resultados: o caso UEPP - Villani, Anita (2013)
This study aims to propose measures on people management to enhance UEPP´s (Priority Projects Delivery Unit) work, created by São Paulo State´s Government. Its focus is improvement in allocation, integration and motivation of the Unit´s current team. Therefore, through interviews and monitoring the work team´s routine, we completed the Unit´s processes mapping and analised each position´s profile, the skills needed to perform the activities, as well as the ideal Unit´s structure. From the information collected, we identified the most relevant problems and proposed measures to improve the Unit´s performance, which can be aggregated into six groups: 1) Unit´s consolidation in São Paulo State´s Government; 2) Unit´s Structure; 3) Processes; 4) Systems; 5) People and 6) Motivation.